The dynamics of fish seed production in West Bengal over the years - Pal, Prasenjit (Journal of the Inland Fisheries Society of India, 2019)
In the current study, an attempt has been made to study the trend of fish seed production overthe years and to find the appropriate model to characterize the dynamics of fish seed production not only in West Bengal but also in India. The appropriate trend equation has been identified and it has been evaluated by the model accuracy parameters like R2 and AIC. The importance of such studies stems from the fact that the policy makers need the specialized scientific information in the form of advisory services in respect of the dynamics of fish seed production.Keywords Trend, R2, AIC, Dynamics